Efficacy and safety of concomitant immunotherapy and denosumab in patients with advanced non-small cell lung cancer carrying bone metastases: A retrospective chart review - Li, Hong-Shuai; Lei, Si-Yu; Li, Jun-Ling; Xing, Pu-Yuan; Hao, Xue-Zhi; Xu, Fei; Xu, Hai-Yan; Wang, Yan (Frontiers in Immunology, 2022)
Immunotherapy brings great benefit for lung cancer patients. However, resistance is a challenge that we must embrace. To overcome the resistance and expand the population benefiting from immunotherapy, mechanisms of tumor-induced immune-suppression are needed to be explored, and combinatory therapy is expected to be more effective. Synergistic anti-tumor effects were observed in cells and animals when immunotherapy was combined with RANKL inhibitor denosumab. However, clinical benefit and safety of this synergy have not been adequately evaluated in lung cancer. By enrolling 171 patients with lung cancer carrying bone metastases who received bone-targeted therapy, we set up four subgroups (including one experimental group and three control groups) to evaluate the synergistic effect of this combination. The results showed that this combination obtained more tumor responses and longer patients’ survival. Finally, our study showed that denosumab exhibited synergistic anti-tumor efficacy without increased toxicity when used concomitantly with immunotherapy in patients with advanced non-small cell lung cancer carrying bone metastases.